Analysis of Task and Responsibility Distribution among Committee Members in the Singing Competition at Polbeng Business Expo Chapter Two - Mega, Lesta; Rambe, Armita Novriana (RIGGS: Journal of Artificial Intelligence and Digital Business, 2026)
This This study aims to analyze the division of tasks and responsibilities of the Singing Competition committee at Polbeng Business Expo Chapter Two by applying the Planning, Organizing, Actuating, and Controlling (POAC) management function framework. In the context of higher education, campus events play an important role in developing students’ soft skills, particularly communication, teamwork, leadership, and problem-solving abilities. However, the effectiveness of these activities is strongly influenced by how well the committee manages task distribution and coordination, especially when faced with limited human resources. This study employed a qualitative research method with a descriptive approach and was designed as a case study. Data were collected through semi-structured interviews, observation, and documentation involving four committee members with different roles, namely the Project Manager, Secretary, Finance, and Marketing. The data were analyzed using the Miles and Huberman model, which consists of data reduction, data presentation, and conclusion drawing, with POAC used as the main analytical framework. The results show that the division of tasks and responsibilities among committee members was carried out quite effectively despite the limited number of personnel. Planning was conducted from the early stages of preparation, organizing was implemented flexibly according to field conditions, actuating was supported by effective communication and mutual motivation, and controlling was carried out through direct monitoring and post-activity evaluation. Overall, the application of POAC management functions played an important role in supporting the smooth implementation of the Singing Competition and ensuring that committee tasks were carried out in accordance with the event objectives.